ANALISIS KUALITAS PRODUK DAN KUALITAS PELAYANAN BARISTA DI KREMA KOFFIE PEKANBARU - Raika Anisailah; Andi M. Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research aimed to know the analys of barista’s product quality amd service quality at Krema Koffie PekanbaruIn this research, the writer was using the qualitative method tp analyze the problem taken. The data were gotten from 10 (ten) infomants, they were 2 (two) owners of Krema Koffie, 2 (two) Barista of Krema, 3 (three) reguler customers and 3 (three) irreguler customer. The techniques which have been used in this research, were observation, interview and document.Based on the interview result has shown the barista’s product quality and service quality were still needed the improvement.Key words: Product Quality, Service Quality, Barista